2016
DOI: 10.1159/000444453
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hearing Function by Auditory Brainstem Response in Newborn Patients with Hydrocephalus before and after Ventriculoperitoneal Shunt Surgery

Abstract: Background/Aim: There is currently no objective evaluation of hearing in patients with hydrocephalus (HCP), and we could not find any study in the literature comprising a sufficient number of patients with a high level of scientific evidence. In the current study, we used the auditory brainstem response (ABR) test to assess whether hearing function in patients with HCP is altered after ventriculoperitoneal shunt surgery. Methods: In total, 20 newborn patients with HCP (13 female, 7 male) were enrolled in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…These findings suggested that peripheral and central hearing loss improved over time which may reflect cochlear and brainstem nerve dysfunction was due to the effects of altered CSF pressure. 14 Of the 70 studied patients, 17 (24%) had hearing loss (10 bilateral and 7 unilateral), and all of them had sensorineural hearing loss, which was associated with low weight at birth, post-hemorrhagic hydrocephalus and brainstem symptoms at the time of diagnosis of hydrocephalus. Hearing pathology was found more often in shunt-treated patients with normal neuro-psychological development (NPD) retardation, poor functional status and low quality of life.…”
Section: Results Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These findings suggested that peripheral and central hearing loss improved over time which may reflect cochlear and brainstem nerve dysfunction was due to the effects of altered CSF pressure. 14 Of the 70 studied patients, 17 (24%) had hearing loss (10 bilateral and 7 unilateral), and all of them had sensorineural hearing loss, which was associated with low weight at birth, post-hemorrhagic hydrocephalus and brainstem symptoms at the time of diagnosis of hydrocephalus. Hearing pathology was found more often in shunt-treated patients with normal neuro-psychological development (NPD) retardation, poor functional status and low quality of life.…”
Section: Results Discussionmentioning
confidence: 96%
“…Some investigators reported the incidence and characteristics of hearing loss in patients with CSF shunt, while other studies and case reports described the onset or resolution of hearing loss with CSF shunting. 14 The Edwards study cited by Satzer et al 11 , compared ABR outcomes between newborns with congenital hydrocephalus and controls. Eleven of 16 (69%) hydrocephalus infants showed ABR abnormalities on initial testing.…”
Section: Results Discussionmentioning
confidence: 99%